Conflitos e negociação de identidade em terras gaúchas / Conflicts and identity negotiation in south Brazilian lands - Lia, Cristine Fortes (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2013)
A vida das comunidades judaicas na Europa, no final do século XIX, estava inviável. As permanentes tensões, em diferentes regiões europeias, promoveram a busca por lares nacionais na América. Dessa forma, no início do século XX foram fundadas, no Rio Grande do Sul, colônias agrícolas para imigrantes judeus, constituindo o período oficial de imigração judaica para o Brasil. O projeto das colônias agrícolas foi marcado por várias dinâmicas, como a inabilidade dos referidos indivíduos com o trato da terra, que caracterizaram a comunidade imigrante de forma negativa. Além disso, pessoas religiosamente distintas, ou seja, não católicas, não eram bem vindas ao Brasil das primeiras décadas do século XX. As formas de instalação na vida rural, as tentativas de rompimento com a mesma, a negociação para permanecer no Brasil e, principalmente, a necessidade de manter sua religiosidade, evidenciando a natureza positiva da mesma, foram marcas do processo imigratório judaico para o Brasil. Este estudo se ocupa da análise das estratégias desenvolvidas por este grupo de imigrantes para garantir sua permanência em cidades brasileiras do sul, destacando o universo religioso que, rejeitado pela sociedade local, transformou-se no foco de conflitos vivenciado pela comunidade. Abstract The life of Jew communities in Europe, by the end of the 19th century, was unviable. The permanent stresses, in different regions of Europe, encouraged people to search for national homes in America. Therefore, agricultural colonies for Jewish immigrants were established in Rio Grande do Sul in the beginning of the 20th century, constituting the official period of Jewish immigration to Brazil. The project of agricultural colonies was marked by many dynamics, like the inability of those individuals to work the land, which characterized the immigrant community as something negative. Furthermore, religiously different people, in other words, not Catholic, were not welcome in Brazil in the first decades of the 20th century. The ways of settling in the rural life, attempts to break up with it, the negotiations to stay in Brazil and, mainly, the necessity of maintaining their religiosity and of evidencing its positive nature were all traces of the process of Jewish immigration into Brazil. This study is concerned with the analysis of the strategies this group of immigrants developed to ensure their stay in South Brazilian cities, highlighting the religious universe that, rejected by the local society, transformed itself in the target of the conflicts that were experienced by the community.